FAKTOR-FAKTOR YANG MEMENGARUHI INTENSI INTRAPRENEURSHIP MAHASISWA PENDIDIKAN AKUNTANSI: THEORY OF PLANNED BEHAVIOUR - Devilla Septianti; Susilaningsih Susilaningsih (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2026)
This study aims to determine 1) the effect of attitude on the intrapreneurship intention of Accounting Education students; 2) the effect of subjective norms on the intrapreneurship intention of Accounting Education students; 3) the effect of perceived behavioral control on the intrapreneurship intention of Accounting Education students; 4) the effect of attitude, subjective norms, and perceived behavioral control on the intrapreneurship intention of Accounting Education students. The study employs a survey research design with a causal-assosiative approach. Sampling used a proportionate stratified random sampling technique. The data analysis technique used descriptive analysis and multiple regression analysis. The results of the study showed that 1) attitude significantly influences the intrapreneurial intention of Accounting Education students; 2) subjective norms do not significantly affect the intrapreneurship intention of Accounting Education students; 3) perceived behavioral control significantly affects the intrapreneurship intention of Accounting Education students; 4) attitude, subjective norms, and perceived behavioral control significantly affect the intrapreneurship intention of Accounting Education students. Keywords: Attitude; Intrapreneurship; Subjective Norms; Perceived Behavioral Control; Theory of Planned Behaviour